Highly-sensitive and Selective Nitric Oxide Sensor Based on Electrolytically Exfoliated Graphene/Flame-spay-made SnO2 Nanocomposite Films - Nantikan Tammanoon (Science Faculty of Chiang Mai University, 2019)
In this work, 0−5wt % electrolytically exfoliated graphene/flame-spray-made undoped SnO2 nanocomposites were systematically studied for NO sensing at low working temperatures. Characterizations by X-ray diffraction and transmission/scanning electron microscopy demonstrated that multilayer graphene sheets were widely distributed within spheriodal nanoparticles having polycrystalline tetragonal SnO2 phase. The sensing films fabricated by powder pasting and spin coating techniques were tested toward 0.125−5 ppm NO at temperatures ranging from 25°C to 350°C in dry air. Gas-sensing results showed that the optimal graphene loading level of 0.5 wt% provided an ultrahigh response of ~7,275 toward 5 ppm of NO and good recovery stabilization at a low optimal operating temperature of 200°C. Furthermore, the sensors displayed high NO selectivity against NO2, H2, C3H6O, H2S and CH4. Therefore, the electrolytically exfoliated graphene-loaded FSP-made SnO2 sensor is a highly promising candidate for sensitive and selective detections of NO in biomedical diagnostic applications.posite Films